2012
DOI: 10.1155/2012/268013
|View full text |Cite
|
Sign up to set email alerts
|

State Anxiety Is Associated with Cardiovascular Reactivity in Young, Healthy African Americans

Abstract: Although several studies have shown that enhanced cardiovascular reactivity can predict hypertension development in African Americans, these findings have not been consistent among all studies examining reactivity and hypertension susceptibility. This inconsistency may be explained by the influence of anxiety (state and trait) on the blood pressure response to stress. Therefore, this study sought to determine whether anxiety is associated with blood pressure response to cold pressor (CP) and anger recall (AR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…7 One possible explanation for the lack of association is the small sample size and consequent lack of power to detect possible effects, although studies of a similar size reported significant positive correlations. 3,5 Finally, other studies have found that anxiety and depressive symptoms are associated with blunted physiological reactivity. In the largest study to date, Carroll et al 8 assessed depressive symptoms in 1,608 adults.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…7 One possible explanation for the lack of association is the small sample size and consequent lack of power to detect possible effects, although studies of a similar size reported significant positive correlations. 3,5 Finally, other studies have found that anxiety and depressive symptoms are associated with blunted physiological reactivity. In the largest study to date, Carroll et al 8 assessed depressive symptoms in 1,608 adults.…”
Section: Introductionmentioning
confidence: 95%
“…For example, Pointer et al reported that state anxiety was positively associated with blood pressure (BP) responses to cold pressor and anger recall in 50 healthy adults. 5 In another study of 60 healthy young women who completed a speech task, depressive symxptoms were positively associated with BP, heart rate (HR), and cardiac output (CO) responses. 3 Thus, these studies suggested that there may be a weak, positive relationship between depressive/anxiety symptoms and cardiovascular reactivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High depression scores were also associated with attenuated blood pressure and electrodermal reactivity to the cold pressor test in female college students (Schwerdtfeger & Rosenkaimer, ). However, other studies found that the parasympathetic or sympathetic autonomic response patterns were not related to worry (Knepp & Friedman, ), or that anxiety was associated with an increased blood pressure and heart rate response to cold stress (Pointer et al., ).…”
mentioning
confidence: 96%